Dual-wavelength mid-infrared CW and Q-switched laser in diode end-pumped Tm, Ho:GdYTaO4 crystal. (10th January 2018) - Wang, Beibei; Gao, Congcong; Dou, Renqin; Nie, Hongkun; Sun, Guihua; Liu, Wenpeng; Yu, Haijuan; Wang, Guoju; Zhang, Qingli; Lin, Xuechun; He, Jingliang; Wang, Wenjun; et al.
Abstract: Dual-wavelength continuous-wave and Q-switched lasers are demonstrated in a Tm, Ho:GdYTaO4 crystal under 790 nm laser diode end pumping for the first time to the best of our knowledge. The laser operates with a dual wavelength at 1949.677 nm and 2070 nm for continuous-wave with a spacing of about 120 nm. The maximum output power is 0.332 W with a pump power of 3 W. By using graphene as the saturable absorber, a passively Q-switched operation is performed with a dual-wavelength at 1950.323 nm and 2068.064 nm with a wavelength interval of about 118 nm. The maximum average output power of the Q-switched laser goes up to 200 mW with a minimum pulse duration of 1.2 µ s and a maximum repetition rate of 34.72 kHz.